Topographic Anatomy of the Abdomen of the Lesser Mousedeer (Tragulus javanicus) - Richardson, K. C.; Vidyadaran, M. K.; Fuzina, N. H.; Azmi, T. I. (1988)
A description is given of the gross anatomy supplemented by radiographic studies of the abdominal structures of (T. javanicus). The large sacculated stomach complex is the dominant feature of the abdomen, it occupies most of the left side and extends across to fill the ventral right side. The intestine is primarily relegated to the dorsal caudal quadrant immediately cranial to the cranial pelvic aperture. The multilobed liver lies entirely on the right. The kidneys are not lobed, with the cranial pole of the right kidney abutting the caudate lobe of the liver and the left kidney lying adjacent but immediately caudal to its fellow. The small triangular spleen lies on the dorsal cranial aspect of the dorsal sac of the rumen.